The Simpsons, Satire, and American Culture - Henry, M.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2012)
How is The Simpsons a satirical artwork engaged with important social, political, and cultural issues? In time for the twenty-fifth anniversary, Henry offers the first comprehensive understanding of the show as a satire and explores the ways in which The Simpsons participates in the so-called "culture war" debates taking place in American society.
Keywords: Motion pictures—History.; Communication; Motion pictures and television; Culture—Study and teaching; Cultural studies; Sociology; Film History; Media Studies; Screen Studies; Regional and Cultural Studies; Cultural Studies; Media Research